Adaptation And Validation Of The Malay-chrononutrition Profile Questionnaire To Assess Chrononutrition Behavior Of Young Adults In Malaysia - Khairunnisa Fazira Hairudin; Nur Islami Mohd Fahmi Teng; Norsham Juliana (Elsevier, 2024)
Indexed by Scopus